2008
DOI: 10.1103/physrevb.78.035424
|View full text |Cite
|
Sign up to set email alerts
|

Self-aligning atomic strings in surface-supported biomolecular gratings

Abstract: We demonstrate the one-dimensional ordering of Co and Fe atoms employing supramolecular templates. Our low-temperature scanning tunneling microscopy observations reveal how individual adatoms spontaneously align with a preferred ϳ25 Å next-neighbor spacing in self-assembled methionine nanogratings on Ag͑111͒. For Co strings the pertaining equilibrium statistics and dynamics were monitored to assess the underlying long-range interactions with their anisotropic energy landscape. The effect of the surface-state e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…33; however, with this system, the flexibility of the constituting porphyrins plays an important role. A potential pathway that could mediate a correlated dynamics is given by the indirect electronic interactions due to surface state scattering on the network and confined objects, which has been exploited to steer the alignment of adatoms in supramolecular gratings on the same substrate in the past (34,35). However, with these systems, there was similarly no evidence for a correlated translational motion or lateral organization in adjacent 1D furrows (34,35), presumably because there is little crosstalk between areas separated by molecular rims (34)(35)(36).…”
Section: Resultsmentioning
confidence: 85%
“…33; however, with this system, the flexibility of the constituting porphyrins plays an important role. A potential pathway that could mediate a correlated dynamics is given by the indirect electronic interactions due to surface state scattering on the network and confined objects, which has been exploited to steer the alignment of adatoms in supramolecular gratings on the same substrate in the past (34,35). However, with these systems, there was similarly no evidence for a correlated translational motion or lateral organization in adjacent 1D furrows (34,35), presumably because there is little crosstalk between areas separated by molecular rims (34)(35)(36).…”
Section: Resultsmentioning
confidence: 85%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Some organic molecules have the ability to self-assemble in two-dimensional ͑2D͒ networks when they are deposited on a surface. Some properties of these templates, such as their possibility to form either chiral or non-chiral ordered structures, 13,14 have been intensively studied for understanding their possible applications in nanotechnology ͑e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Earlier studies have already demonstrated that metallic substrates can indeed mediate long-range interactions and influence atomic and molecular ordering. Examples include shells of atoms, 41 zwitterionic nano gratings, 42 the self-aligned atomic strings in bimolecular gratings, 43 and porous networks of anthraquinone molecules. 44 Reported energies for substratemediated interactions are of the order of one or more milli electron volts over a distance of a few nanometers (see overview in Ref.…”
Section: Long-range Surface-mediated Interactionsmentioning
confidence: 99%